Supervised and Unsupervised Parental Access in Domestic Violence Cases in New York City, New York, 2002-2005 - O'Sullivan, Chris ([Verlag nicht ermittelbar], 2009)
The purposes of this study were (1) to examine factors associated with New York City Family Courts' visitation decisions and conformity to the provisions of the Model Code of the National Council of Juvenile and Family Court Judges when there was a history of abuse of the mother by the father, (2) to compare the different visitation conditions in regard to reabuse -- both psychological and physical, and (3) to examine children's psychological well-being as measured by maternal report on the Child Behavior Checklist (CBCL), given their exposure to abuse. Two hundred forty-two participants were recruited from the Family Courts and supervised visitation centers in the five counties in New York City. Interviews were conducted in English and Spanish. There were two interviews with the mother, with an average interval of six months between interviews. Baseline interviews were conducted in person, at the court, or visitation center from 2002 to 2004. Follow-up interviews were conducted with 168 of the participants from 2003 to 2005 and were conducted over the phone, except on the rare occasions when a participant requested an in-person interview. Information in the the baseline interview included demographic information on the participant as well as on the father of the child(ren), information on the level of physical violence and the children's exposure, how often particular acts of violence took place, threats and coercion, an injury index, information regarding court orders, information regarding custody petitions, information regarding visitation orders, and visitation experience. The follow-up interview asked about abuse since the previous interview and included updates, changes, and modifications to the information provided in the baseline interview.